Web-application development projects by online communities: Which practices favour innovation?. Issue 1 (6th February 2017) - Annarelli, Alessandro; Battistella, Cinzia; Nonino, Fabio
Abstract : Purpose: The purpose of this paper is to propose an in-depth analysis of online communities of practice that support the innovative development of web applications. The analysis is aimed at understanding the preeminent characteristics of communities of practice that can favour the process of innovation (conceptualisation and realization of a web application) and if these characteristics differ in the diverse phases of a software development project (requirement specification, design, implementation and verification). Design/methodology/approach: The authors adopted a multiple case study research design, selected 29 communities of practice related to the development of web applications and classified them recognizing the different practices that refer to the different phases of the innovation process of web-applications software development. Finally, the authors focussed on seven communities comparing five important dimensions for each one. Findings: The results of the empirical analysis show that the best practices are different, considering the different phases of the project, and that these practices can be strategies directed at members to attract them and also, strategies directed at the community to permit collaboration. Originality/value: The paper proposes an important and new insight into the management of virtual communities of practice (VCoP). The authors supposed that the ways to manage a VCoP could depend on project phases. In particular, the management practices of community should differ according to the different project phases, i.e. requirements specification, design, implementation and verification of the software. Literature in this sense presented only research focussed on the different effects of virtualness on teams depending on the length of team duration and on communication efforts.